Cyclical hypofractionated radiotherapy also known as "QUAD Shot" alone using intensity‐modulated radiotherapy for squamous cell carcinoma of the parotid gland in an 85‐year‐old patient with multiple comorbidities. Issue 4 (7th February 2017) - Kil, Whoon Jong; Camphausen, Kevin
ABSTRACT: Background: Palliative radiotherapy (RT) is not commonly offered to patients with head and neck cancer because of the belief that toxicity from the RT would not provide great palliative benefits. The purpose of this study was for us to report the advantages of cyclical hypofractionated RT (QUAD Shot) using intensity‐modulated RT (IMRT) for an elderly comorbid patient with head and neck cancer. Methods: An 85‐year‐old multiple comorbid man with squamous cell carcinoma in the left parotid gland with left facial pain received the IMRT‐QUAD Shot (14 Gy/4 fractions, twice‐daily treatment with 6 hours interval, on 2 consecutive days) to lesions, which were repeated every 4 weeks 3 times. Results: With the IMRT‐QUAD Shot, he achieved complete left facial pain relief without acute toxicity. At 12 months after the first IMRT‐QUAD Shot, he remained without left facial pain, late toxicity, or disease recurrence impacting positively on his quality of life. Conclusion: The IMRT‐QUAD shot is reasonable and safe to apply for symptom palliation in elderly multiple comorbid patients with head and neck cancer. 2017 Wiley Periodicals, Inc. Head Neck 39 : E55–E60, 2017